Entrepreneurship for People With Disabilities: From Skills to Social Value - Ortiz García, Pilar; Olaz Capitán, Ángel José (Frontiers in Psychology, 2021)
The social value of entrepreneurship derives from the contribution of this activity to the socio-economic development of the context where entrepreneurship takes place. When the entrepreneurial activity is undertaken among especially vulnerable groups in the labor market, the multiplying effect of this value is made explicit in society in general and in the collective of people with disabilities in particular. The objective of this research study is to explore under which conditions this happens through the analysis not only of the relationship between the competencies that people with disabilities attribute to themselves and their development of the entrepreneurial activity but also that between entrepreneurship and certain conditions that potentially create value by increasing the autonomy among this collective. A quantitative methodology based on the analysis of the survey carried out on a sample of 224 entrepreneurs with physical, sensory, or organic disabilities throughout Spain has been used. According to the results, entrepreneurs with disabilities have a higher self-evaluation competency. Furthermore, significant results concerning the link between the form of autonomous cohabitation of this collective and entrepreneurship have been obtained.